1993
DOI: 10.1172/jci116912
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor inhibits bone regeneration induced by osteogenin, a bone morphogenetic protein, in rat craniotomy defects.

Abstract: Platelet-derived growth factor (PDGF) is a potent moderator of soft tissue repair through induction of the inflammatory phase of repair and subsequent enhanced collagen deposition. We examined the effect of recombinant BB homodimer PDGF (rPDGF-BB) applied to rat craniotomy defects, treated with and without bovine osteogenin (OG), to see if bone regeneration would be stimulated. Implants containing 0, 20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 34 publications
2
37
1
1
Order By: Relevance
“…A number of studies have investigated combination treatment with PDGF and several other growth factors including bFGF (Meraw et al, 2000), BMP-2 (Martino et al, 2011), BMP-7 (Zhang et al, 2009b, IGF-1 (Nociti Junior et al, 2000), osteogenin (Marden et al, 1993), TGF-β1 and VEGF (El Backly et al, 2013). Bone formation was reported to increase between 1.4 and 2.3 fold (Zhang et al, 2009b) within large animals (dog (Zhang et al, 2009b)) following PDGF dosages around 5 µg/mL for direct administration (Nociti Junior et al, 2000), or 2 x 10 10 / mL viral particles for indirect administration (Zhang et al, 2009b).…”
Section: Combination Administration Of Pdgfmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have investigated combination treatment with PDGF and several other growth factors including bFGF (Meraw et al, 2000), BMP-2 (Martino et al, 2011), BMP-7 (Zhang et al, 2009b, IGF-1 (Nociti Junior et al, 2000), osteogenin (Marden et al, 1993), TGF-β1 and VEGF (El Backly et al, 2013). Bone formation was reported to increase between 1.4 and 2.3 fold (Zhang et al, 2009b) within large animals (dog (Zhang et al, 2009b)) following PDGF dosages around 5 µg/mL for direct administration (Nociti Junior et al, 2000), or 2 x 10 10 / mL viral particles for indirect administration (Zhang et al, 2009b).…”
Section: Combination Administration Of Pdgfmentioning
confidence: 99%
“…Bone formation was reported to increase between 1.4 and 2.3 fold (Zhang et al, 2009b) within large animals (dog (Zhang et al, 2009b)) following PDGF dosages around 5 µg/mL for direct administration (Nociti Junior et al, 2000), or 2 x 10 10 / mL viral particles for indirect administration (Zhang et al, 2009b). Combination treatments within small animal (mouse (El Backly et al, 2013), rabbit and rat (Park et al, 2013)) studies reported increased bone formation between 2.5 (Xu D Gothard et al Tissue engineered bone and clinical translation et al, 2012) and 10 fold following PDGF dosages ranging between 0.05 (Martino et al, 2011) and 200 µg (Marden et al, 1993).…”
Section: Combination Administration Of Pdgfmentioning
confidence: 99%
“…1a, b Plain radiograph (a) and CT scan section (b) of the spine of pig 6 after 3 months. L2/3 was graded partial fusion into which autograft was put; beta tricalcium phosphate (β-TCP) was put into L4/5 where the radiograph shows non-fusion and the CT image shows partial fusion; β-TCP loaded with platelet-rich plasma (PRP) was in the lowest level (L6/7) where particles of β-TCP can still been seen failed to achieve significant increase in bone ingrowth into HA carriers in rat femora [1] and PDGF even inhibits bone regeneration induced by osteogenin in rat calvarial defects [16]. Other factors released by platelets, such as EGF and IGF, also demonstrate positive effects on osteoblast or bone formation [17,24].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of PDGF have been studied in animal models of cranial and alveolar-ridge defects (11)(12)(13)(14)(15)(16)(17)(18)(19). However, these studies yielded conflicting results regarding promotion of new bone formation.…”
Section: Introductionmentioning
confidence: 99%